Evaluation of vitamin D status, parathyroid hormone, and calcium among Iranian pregnant women with preeclampsia: A case-control study - Laaya Hamedanian; Bita Badehnoosh; Niloofar Razavi-Khorasani; Zinat Mohammadpour; Hassan Mozaffari-Khosravi (Shahid Sadoughi University of Medical Sciences, 2019)
Background Preeclampsia is considered as a serious life-threatening condition that could affect both maternal and fetal outcome. Many studies have examined the association of nutritional factors with the incidence of preeclampsia. However, little is known about the possible role of vitamin D in the development of preeclampsia among the Iranian population. Objective The aim of the present study was to evaluate the association between vitamin D status and preeclampsia Materials and Methods A total of 120 pregnant women who were referred to Kamali and Alborz General Hospital located in the Karaj City were enrolled in this study and categorized into preeclamptic and control groups (n = 60/each). The clinical details of patients such as demographic characteristics and laboratory findings were obtained from the patients. The serum levels of vitamin D, calcium, phosphorus, and parathormone were also measured. Multivariate logistic regression analysis was used to assess for independent predictors of preeclampsia. Results The mean age among pregnant women with preeclampsia and control group were 31.48 ± 5.25 and 29.01 ± 5.28, respectively. The mean body mass index among the preeclamptic group was 27.92 ± 4.98, which was significantly higher compared to the control group (p < 0.001). The serum vitamin D levels were significantly lower in women with preeclampsia compared to the control subjects (p = 0.007). Moreover, no correlation between vitamin D deficiency and predisposing factors of preeclampsia was observed after adjusting for confounding factors. Conclusion Our study revealed that serum vitamin D level is significantly lower in among the pregnant women diagnosed with preeclampsia compared to the healthy subjects. However, no correlation was observed between the vitamin D status and the risk of preeclampsia development.